Overweight and Obesity and its Associated Factors Among Office Staff at a Higher Education Institute in Malaysia. - Zabuddin, Nurul Aini Binti Mohamad; Jamaludin, Mohamad Aiman Arief Bin; Pasha, Mehboob Alam; Salam, Abdus (Bangladesh Journal of Medical Science, 2023)
Introduction: Overweight and obesity caused by excess body fat accumulation is a leading public health problem globally. The objective of this study was to investigate the overweight and obesity prevalence and its accompanying factors among educational office staff in Kuantan, Malaysia. Materials and Methods: A cross-sectional study was conducted among the staff of Widad University College (WUC) and Widad College (WC) using a self-administered validated questionnaire. Socio-demographic characteristics of the participants and obesity-related health information such as body mass index (BMI), smoking, alcoholics, physical activities and blood pressure status were obtained. The BMI was determined considering the participants weight in kilograms (kg) divided by the square of height in meters (kg/m2). Correlating the BMI with sociodemographic and health-related factors, the participants were characterized as underweight, normal, overweight and obese and presented as mean, frequency and percentage distribution. A p-value of <0.05 means a statistically significant result. Results: Overweight prevalence was 28.3% while obesity was 16.2 %. There were 13% of respondents underweight. A higher rate was found in males and Malay participants. Age, education, occupation, income, smoking, alcoholics, physical inactivity and hypertension were significantly linked to BMI. Conclusions: Overweight and obese constitute around 44% of the staff at WUC and WC, while 13 % were underweight. It is necessary to motivate employees through an effective training program organized by the employer towards maintaining a healthy lifestyle and thereby maintaining good health and improving work performance. Bangladesh Journal of Medical Science Vol. 22 No. 04 October’23 Page : 833-841